2020
DOI: 10.3390/jfmk5010004
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Asparagus Racemosus Supplementation Plus 8 Weeks of Resistance Training on Muscular Strength and Endurance

Abstract: Previous studies have demonstrated that ayurvedic ingredients exhibit ergogenic (performance enhancing) properties, however, no previous studies have examined the ergogenic potential of Asparagus racemosus. The purpose of the present study was to examine the ergogenic efficacy of supplementation with 500 mg·d−1 of A. racemosus during bench press training. Eighteen recreationally trained men (mean ± SD; age = 20.4 ± 0.5 yrs; height = 179.7 ± 1.5 cm; weight = 84.7 ± 5.7 kg) were randomly assigned either 500 mg·d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 29 publications
(64 reference statements)
3
17
0
Order By: Relevance
“…The mean values for the dietary intake parameters in the present study were similar to those from recent studies [23,53], but somewhat lower than expected for this sample [54]. This was likely due to the systematic underreporting of nutritional intake from the dietary recall form [55].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The mean values for the dietary intake parameters in the present study were similar to those from recent studies [23,53], but somewhat lower than expected for this sample [54]. This was likely due to the systematic underreporting of nutritional intake from the dietary recall form [55].…”
Section: Discussionsupporting
confidence: 83%
“…Evidence regarding the use of antioxidants have reported equivocal reports, including studies suggesting that antioxidants may blunt cellular mechanisms associated with adaptation and recovery [44,45]. Antioxidant supplementation, however, has been demonstrated to improve strength [23,46] and power [47], as well as delay the effects of fatigue [23,48] and enhance recovery following eccentrically induced muscle damage [49]. Thus, theoretically, the blend of phosphocreatine, blueberry extract, and sodium may have had synergistic effects that resulted in significant improvements in exercise performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The copyright holder for this this version posted September 20, 2021. ; https://doi.org/10.1101/2021.09.16.21263687 doi: medRxiv preprint Despite these caveats, we have demonstrated novel functional effects of shatavari supplementation in skeletal muscle, along with some important mechanistic insights. We consider that the potential for shatavari supplementation to enhance muscle protein synthesis should be further explored in longer-term resistance training studies, given our evidence of Akt Ser473 phosphorylation following shatavari supplementation, coupled with the observations of Anders et al that shatavari enhanced strength gains in young men following eight weeks of bench press training [17]. Indeed, the balance of current evidence suggests that E2 increases the anabolic response to exercise over the longer term (for an excellent review see [42].…”
Section: Discussionmentioning
confidence: 99%
“…E2 withdrawal has a detrimental effect on myosin binding function and therefore muscle force production; conversely E2 improves muscle force production, and may promote muscle protein synthesis [14][15][16]. One study has shown that shatavari (500 mg•d −1 root extract; fresh weight equivalent not stated) enhanced strength gains in young men following eight weeks of bench press training [17]; this was an observational study with no indication of possible mechanisms of action. However, it does suggest that shatavari may be a beneficial ergogenic aid in supporting resistance training-induced increases in muscle size and strength; no assessment of these ergogenic effects has been made in older adults.…”
mentioning
confidence: 97%